Anesthesia Nurses' Perceptions of Anesthesiology Nursing Care Method - Putu Atika Parwati (Indonesian Journal of Global Health Research, 2025)
Anesthesia care is a comprehensive series of care activities for patients who are unable to help themselves during pre-, intra-, and post-anesthesia procedures. The quality of an anesthesiologist can be seen in the provision of anesthesia nursing care. This study aims to determine the perceptions of anesthesiologists in Indonesia regarding anesthesiology nursing care. The research design used was descriptive research with a cross-sectional approach. The population sampled was anesthetists in Bali. Univariate analysis was performed by determining the frequency distribution and percentage of anesthetists' perceptions of anesthesiology nursing care. This study used a questionnaire regarding anesthesiologists' perceptions of anesthesiology nursing care methods with a Cronbach Alpha value of 0.634. The results of the study concluded that the perception of anesthesiologists regarding major anesthesiology nursing care methods was mostly in the good category, namely 64 people (64.6%), while those in the adequate category were 36 people (36.0%).